Invasion of Hovenia dulcis Thunb. (Rhamnaceae) in Southern Brazilian subtropical forest - Dionatan Gerber; Paula Helena Pereira O’connor; Hiuller Vasconcellos Mendonça; Gilmar Poser Brizola; Álvaro Rodrigo Freddo; Fernando Campanhã Bechara (Acta Biológica Catarinense, 2018)
This study aimed to evaluate the level of Hovenia dulcis (oriental-raisin-tree) invasion in an area under ecological restoration (area 1) and in a fragment area of araucaria forest with semi-deciduous seasonal forest (area 2), both located in the municipality of Dois Vizinhos, Paraná. In 1, the techniques of passive restoration, nucleation and plantation of high diversity of tree species were analyzed. In 2, there was a survey of young and adult individuals. In 1, 12 plots of 2,160 m² were sampled (25,920 m² sampled). In 2, 30 plots with an area of 30 m² each were sampled (900 m² sampled). In 1, the greatest proliferation of the species, with density of 334.5 plants.ha-1, was observed in a period of 17 months. In 2, the invasive potential of H. dulcis was high, with a mean of 911 young plants.ha-1 and 111 adult plants. ha-1. Higher invasive capacity occurred in areas of initial and secondary stages of secondary succession. Sites that present hydromorphic soils and especially those where there are pteridophyte, bromeliaceae and bambusoid groups, practically prevent the development of young individuals of H. dulcis. The species presents great invading potential in areas under ecological restoration and in forest fragments, thus, attention in the monitoring and control of the species is recommended.